Adherence to prompt fever evaluation in children with sickle cell disease and the health belief model. Issue 11 (14th July 2015) - Schultz, Corinna L.; Tchume‐Johnson, Trudy; Schapira, Marilyn M.; Bellamy, Scarlett; Smith‐Whitley, Kim; Ellison, Angela
<x xml:space="preserve">Abstract</x> Background Children with sickle cell disease (SCD) are at increased risk of death from invasive bacterial infections. Emergent evaluation of fever allows early treatment of potentially fatal infections. Limited data exist regarding caregiver adherence to physician recommendations of prompt medical evaluation of fever in children with SCD. Better understanding of parental behavior around fever management may inform improved models for support in families of children with SCD. Procedure Cross‐sectional survey based on health belief domains, Wake Forest trust scales, and self‐reported adherence among 163 caregivers of children with SCD during routine hematology visit. Results Fifty‐five percent of caregivers were adherent to fever evaluation recommendations as defined by "always" seeking medical evaluation of fever in their child with SCD. Perceived susceptibility to fever/infection, benefits of prompt evaluation, and cues to action were significantly different between those who adhere to recommendations versus those who do not. Twenty‐five percent believe their child does not need antibiotics with every fever whereas 17% believe their child does not need evaluation of fever after immunizations. Fifty‐seven percent report their employer understands missing work whereas 25% report concern regarding cost of evaluation. Trust in their child's hematologist and medical profession was high (composite scores 23.4/25 and 21/25, respectively). Conclusion Despite a high degree of agreement in importance of fever evaluation and high levels of trust, many caregivers do not consistently seek care when their child has a fever. Future studies should address additional barriers to seeking emergency care in children with SCD and fever. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.